(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This paper explores how role-playing activities help children develop soft skills while learning to speak English. The study analyzes data from previous research involving young learners aged eight to ten in elementary schools. The role play used is simple and age-appropriate, allowing children to act out scenarios without fixed dialogues, relying instead on their creativity and understanding. The findings show that role play enhances communication, problem-solving, analytical thinking, decision-making, and self-confidence in speaking English as a second language.